First-in-human exploratory trial assessing safety, feasibility, and efficacy of artificial protein (silk-elastin) in promoting healing in patients with meniscus injuries - Ishikawa, Masakazu; Tsuji, Shunya; Kamei, Goki; Nakata, Kyohei; Nekomoto, Akinori; Hashiguchi, Naofumi; Nakasa, Tomoyuki; Nakamae, Atsuo; Kamei, Naosuke; Inoue, Keiichiro; Kawabata, Shingo; Ueda, Keiko; et al. (Scientific reports, 2025)
Meniscal tears, especially those in avascular regions, pose a significant risk for osteoarthritis if repair fails. While meniscal repair is the preferred method for preserving knee function, it often has a high failure rate in avascular zones. This study aimed to evaluate the safety and potential efficacy of silk-elastin (SE), an artificial protein with wound-healing properties, for enhancing meniscal repair. Eight patients with meniscal tears in avascular areas underwent arthroscopic repair followed by SE application, including cases of lateral and medial tears, discoid lateral meniscus, and bucket-handle tears. No adverse events or reactions were attributed to SE. At 3 months post-surgery, clinical outcomes and repair sites were evaluated using MRI and arthroscopy. Significant improvements were observed in Lysholm and visual analog scale scores ( P < 0.05), with the knee injury and osteoarthritis outcome scores showing significant improvement in the symptom subscale. MRI findings indicated one patient with grade 1 healing, three with grade 2, and four with grade 3 (unhealed). Arthroscopically, six patients demonstrated completely healed menisci, while two showed incomplete healing; none were classified as “unhealed.” These findings suggest that SE is safe and may support meniscal healing in avascular zones, indicating its potential to improve repair outcomes.